FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT DI RUMAH SAKIT PERTAMINA BINTANG AMIN KOTA BANDAR LAMPUNG TAHUN 2018 - Esteria Marhayuni (PSIKOLOGI KONSELING, 2021)
Nurses as one of the health workers in hospitals play an important role in efforts to achieve health development goals. Based on data from the Public Relations department of Pertamina Bintang Amin Hospital, it was found that inpatient satisfaction was 75%. below the minimum service standard (SPM) indicator for inpatient care, which is 90%. Based on the results of Human Resources (HR) monitoring there are several complaints submitted by patients regarding nurse's performance so that it decreases patient satisfaction, the complaints submitted are: nurses who are not responsive to patient complaints by (56.7%). This study aimed to is known factors - factors related to the performance of nurses at Pertamina Bintang Amin Hospital in 2018. A quantitative research, with Cross Sectional approach, conducted among 118 nurses at Pertamina Bintang Amin Hospital taken by Proportional random sampling. Data collection using questionnaires, data analysis in univariate, bivariate (Chi Square) and multivariate (Logistic Regression). The results of the study showed good performance 67.8%, strong motivation 64.4%, job satisfaction satisfied 69.5%, compensation 66.9%, good leadership 62.7% and good organizational culture 83.1%. There is a relationship of motivation (p-value = 0,000; OR 21,250), job satisfaction (p-value= 0,000; OR 15,167), compensation (p-value = 0,000; OR 6,133), leadership (p-value= 0.000; OR 7,463), organizational culture (p-value 0.001; OR 5.423) with performance. The dominant factor in the performance of nursing staff was motivation (p = 0.001; OR 6.358). Giving awards in the form of incentives so that they are expected to be a motivator for nurses to improve their performance. Provide opportunities for nurses to attend training and seminars in nurse self-development.